The influence of early linguistic skills and family factors on literacy acquisition in Chinese children: Follow-up from age 3 to age 11. (June 2017) - Su, Mengmeng; Peyre, Hugo; Song, Shuang; McBride, Catherine; Tardif, Twila; Li, Hong; Zhang, Yuping; Liang, Weilan; Zhang, Zhixiang; Ramus, Franck; Shu, Hua
Abstract: The present longitudinal study investigated the predictive power of preschool linguistic skills and early family factors on children's comprehensive literacy skills at the end of primary school in 262 Chinese children. The results indicated that a substantial (20–34%) share of variance of 5th grade (age 11) literacy skills in Chinese could be explained by early family factors (age 3) and linguistic skills (age 3–age 5). Family socioeconomic status and parent-child reading tuition were associated with different literacy measures. A differential pattern of prediction was also observed among different literacy skills. Furthermore, path analyses indicated that the relationships between early family factors and literacy skills at age 11 were mediated by specific linguistic and cognitive skills at preschool. Highlights: Preschool linguistic skills and family factors predicted later literacy skills. Cognitive predictors have specific effects depending on each literacy skill. Linguistic skills were mediators between family factors and literacy skills.